The Rule of Benedict for Beginners: Spirituality for Daily Life - Anne, Dänemark, Prinzessin (Implicit religion, 2010)
The article reviews the book "The Rule of Benedict for Beginners: Spirituality for Daily Life," by Wil Derske.